GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 573007582 species occurrences available in GBIF matching the query: HasGeospatialIssue: false HasCoordinate: true. The dataset includes 573007582 records from 12110 constituent datasets: 54866 records from SysTax - Zoological Collections. 2846 records from Coleoptera, NEF. 144 records from Ehmkendorf. 55 records from Waldsee. 71 records from Bolzplatz. 79 records from GymnQuerfurt. 63 records from Erft in Selikum (Neuss). 18 records from Mittelstreifen. 163 records from Brander Wald (Stolberg). 88 records from BIRDRACE Vogelkucker. 30 records from Riekdahler Wiesen. 265 records from Luderbusch. 69 records from Mönchspark. 360 records from Wälder bei Nordkirchen. 1 records from Wildnis Erzental. 2 records from Parthenaue. 968 records from Königstetten. 372 records from Otter survey of Ireland 2004 & 2005. 2522 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 10930 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 1432 records from Naturalis Biodiversity Center (NL) - Crustacea. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 117631 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 30366 records from Oregon State University Herpetological Collection. 8727 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 27932 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 139 records from The Bat Conservation Trust - Woodland Survey. 119 records from Bryozoa of the British Isles. 48828 records from Grey seal at-sea distribution 2009-2014. 6 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 353 records from Coastal and marine species. 53606 records from BioMar - LIFE project. 991 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 36431 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 378 records from Tsetse flies of East Africa update. 212 records from Phthiraptera. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 31879 records from Mollusca of Costa Rica (INBio). 8780 records from Artròpodes d'Andorra. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 57210 records from National Biodiversity Data Bank. Observation records, 1900-2014. 461 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 10674 records from kpabg_lichens. 333 records from Macroarthropods, Isua 2013, Greenland. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 459992 records from Royal Dutch Angling Association (SVN) - Piscaria. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 642 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 55785 records from PRECIS (KwaZulu-Natal Herbarium). 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 46527 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 206 records from The Diptera Site. 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 24453 records from Plan de vertebrados de la Patagonia. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 1 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 2604 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 1484 records from IWDG Constant Effort Cetacean Sighting Scheme. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 2184 records from JOI - Herbário Joinvillea. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 1627 records from University of Calgary Herbarium. 3508 records from Entocytheridae (Ostracoda) World Database. 8 records from Siphonaptera. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 93 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 690 records from Mid Ulster Hare Surveys 2012-2015. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 8220286 records from OEH Atlas of NSW Wildlife. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 168427 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 7008 records from HUEM - Herbário da Universidade Estadual de Maringá. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 19 records from Revision von Suctobelba trigona (Michael, 1888). 29470 records from Phanerogamic Botanical Collections (S). 10000 records from National Lesser Horseshoe Bat Database. 85 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 69751 records from African Rodentia. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 5709 records from Coleoptera of Piska Forest. 355 records from Herbier G. Garapin (BOUM). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 4 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 6885 records from ISE - Herbário ISE. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 99133 records from Landesmuseum Kärnten. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 172165 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 50348 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 1 records from ISM Mammalogy Collection. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1236 records from Insect Collection (CeStuBio). 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 7034 records from Mollusca collection of National Museum of Nature and Science. 3 records from MSB Mammal Observations (Arctos). 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 190 records from Herpetofauna laguna El Tinije. 8927366 records from Botanical Society of the British Isles - Vascular Plants Database. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 9064 records from HUFU - Herbarium Uberlandense. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 13912 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 20 records from Truchas Mexicanas. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 111151 records from Jordal. 252050 records from MVZ Herp Collection (Arctos). 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 4107 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 58938 records from Biological Records Centre - Isopoda (Interim dataset). 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1997 records from Aves de la cuenca media del río Bogotá. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 10552 records from Biological Records Centre - Collembola Recording Scheme. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 3817 records from UFG - Herbário da Universidade Federal de Goiás. 38541 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 1144 records from Colección de Entomología - Diptera - Ceratopogonidae. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 561 records from Herpetile collection, Natural History Museum, University of Oslo. 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 3204 records from Faunal Inventory of Morysin Nature Reserve. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 56720 records from University of Vienna, Institute for Botany - Herbarium WU. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 9302 records from Ants from the Paraguayan dry Chaco. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 1702 records from BioGIS - Bryophytes - HUJ collections. 4791 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 586 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 38567 records from Marine species distributions in Irish coastal waters. 2546 records from The atlas of butterflies in Kraków. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 10075 records from Nematoda of Costa Rica (INBio). 154478 records from Australian National Wildlife Collection provider for OZCAM. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 288 records from Fungi of Słowiński National Park, Poland. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 212 records from Colección nacional de palmas de Colombia - JBQ. 11 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 211700 records from MVZ Mammal Collection (Arctos). 89874 records from ecoscope_observation_database. 4316 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 5864 records from Herbarium Vonderau - FULD. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 7250 records from All Ireland Marsh Fritillary Database. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 423 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 891282 records from PRECIS. 10250 records from Census of the flora of Benin. 998 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 179917 records from LACM Entomology Collection. 140022 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 23 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1015 records from Irish Marine Turtle Database. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 9874 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 2407 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 1211 records from CCBER Herpetology Collection. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 5 records from Order Diptera, family Mydidae. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 4730 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 13566 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 896 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 6800 records from Tromsø Museum, Bryophytes. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 33 records from New records in vascular plants alien to Kyrgyzstan. 506471 records from Consortium of California Herbaria. 38093 records from Online Atlas of vascular plants 2012-2020. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 45217 records from IAC - Herbário do Instituto Agronômico de Campinas. 60131 records from QLD DERM Coastal Bird Atlas (Trial). 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 51297 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 6660 records from Weevils of the Tatra Mts.. 23048 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 546876 records from Bee Biology and Systematics Laboratory. 8302 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 47570 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 3042 records from dec2011. 12220 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 457499 records from Bird Atlas 2007 - 2011. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 554 records from Portuguese Seaweeds. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 527 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 8784 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 25002 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 113964 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 4611 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 1244521 records from AntWeb. 670 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 295987 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 8581 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 214 records from Collection of Heteroptera. 3754 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 176654 records from CAS Entomology (ENT). 8 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 400 records from National Taiwan Ocean University. 2 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 24 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 1 records from Lissotes working-group. 2253 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 22451 records from TCWC Marine Invertebrates. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 9082 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 28172 records from Notes from the Mycology Herbarium, Oslo (O). 1200 records from monocotyledonous_geophytes_of_fergana_valley. 562083 records from Fishbase. 238 records from Irish Federation of Sea Anglers Catch Data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 28772 records from EPA River Biologists data. 2336 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5733 records from Small Mammal Research Database. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 1 records from Red list project inventory, bryophytes. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 2130 records from Zoology (Museum of Evolution - Uppsala). 876791 records from Naturalis Biodiversity Center (NL) - Botany. 100 records from Brock University Herbarium (BU). 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 670341 records from PlutoF platform observations. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 264 records from Herbarium Senckenbergianum (GLM) - Lichenes. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 16774 records from KUBI Ornithology Tissue Collection. 10898 records from SPSF - Herbário Dom Bento José Pickel. 68 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 59522 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 36413 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6198 records from Plecoptera. 10135 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 24403 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 1091 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 2484 records from Marine Environmental Monitoring - Marine Turtles. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 23037 records from CSIRO Ichthyology provider for OZCAM. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1427 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 190 records from Relative abundance of ostracods in sediment core Sv09. 7265 records from NHM, Heteroptera. 715 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 21 records from Hyolithen - SMF. 24889 records from SPF - Herbário da Universidade de São Paulo. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 4965 records from SANT herbarium vascular plants collection. 2 records from Collection Myriapoda - SNSD. 174497 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 164937 records from KUBI Mammalogy Collection. 930 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 103104 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 91719 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 6425 records from Likona Invertebrates. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 101412 records from Occurrence records of southern African aquatic biodiversity. 1163 records from Paläontologie Marburg. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 4432 records from Lepidoptera (Observations). 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 13 records from Perot Museum of Nature and Science. 10306 records from Cercle des mycologues de Montréal Fungarium (CMMF). 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 2107 records from MLZ Mammal Collection (Arctos). 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 628004 records from Inventario Español de Especies Terrestres (MAGRAMA). 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 139243 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 9349 records from Harriet Irving Botanical Gardens (HIBG). 3176 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 9376 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 1432 records from University of Amsterdam (NL) - Páramo pollen reference collection. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 2239160 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 500 records from Colección de Reptiles del Instituto Alexander von Humboldt. 1 records from Herpetology. 891 records from National Museum of Marine Biology and Aquarium. 9855 records from Bibliographic records of Angola mammals. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 17618 records from BioGIS - Mammals - INPA database. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 15 records from Projeto Abrace o Boto Cinza. 328 records from Insect Collection from New Caledonia. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 346 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 61 records from Registros restauración ecológica- Magdalena medio. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 47 records from Empria and Monsoma in Japan. 25945 records from NPL collections. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 751 records from Trichoptera (caddisflies) of Ireland. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 353 records from Colección de Entomología - Arthropoda. 15817 records from UFP - Herbário UFP - Geraldo Mariz. 76858 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3083 records from Finnish Entomological Database: Heteroptera. 4 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 592367 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 35762 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2011 records from Local BioBlitz Challenge 2013. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 47 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 3039 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 2 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 381 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 1159 records from API_CRSN_Data. 6139 records from HERBAM - Herbário da Amazônia Meridional. 23366 records from Herbario Pontificia Universidad Javeriana. 28362 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 22639 records from IICT Herbário LISC. 81747 records from Herbario Universidad de Antioquia (HUA). 1093 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 36972 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 7436 records from URM - Herbário Pe. Camille Torrand. 43881 records from University of Alberta Vascular Plant Herbarium (ALTA). 528 records from Collection Crustacea - KAUMM. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 4 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 883082 records from FLORIVON. 111581 records from Highland Biological Recording Group - HBRG Insects Dataset. 651 records from VMNH Invertebrate Paleontology. 386572 records from Species data extracted from the National Vegetation Database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 2089 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 213 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 19122 records from Biological Records Centre - Cerambycidae Dataset. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 1 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 20422 records from ICN - Herbário do Instituto de Ciências Naturais. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 4025 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 652 records from Spider species diversity from wet and dry habitats. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 3257 records from fundiv france database. 61980 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 231866 records from Lyman Entomological Museum (LEMQ). 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 364 records from published_chenopodium_vulvaria_observations. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 86071 records from NINA Vanndata øvrige arter. 100 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 338 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 71617 records from The avian collection at the Natural History Museum, Oslo, Norway. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 615 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 440 records from NCSM Birds Collection. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 2240 records from Fongs d'Andorra. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 52 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4369 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 69595 records from Lepidoptera collection, Natural History Museum, University of Oslo. 3673137 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 50453 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 945 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 9037 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 9757 records from Collection of Coleoptera. 52 records from Isotope tracer experiment: meiofauna counts. 5053399 records from Southern African Bird Atlas Project. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 611 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 17782 records from The Bat Conservation Trust - Colony Count Survey. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 63 records from (Data S1) Palynology of ODP Site 119-739. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 4853 records from University of Alberta Museums, Entomology Collection. 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 16749 records from IMOS - AusCPR: Phytoplankton Abundance. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 2466 records from TTRS Ornithology. 68110 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 588 records from Relative abundance of ostracods in sediment core Lz1120. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 1 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 30 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 534 records from Ascomycetes of Russian Fennoscandia. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 116639 records from The digitization of plant specimens of NTU. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 991 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 78981 records from NCSM Fishes Collection. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 194 records from Colección Herpetológica de la Patagonia. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 1423 records from Reptilia notes, NTNU, Trondheim. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 55897 records from AM: Freshwater Invertebrates (1900-2005). 721 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 1605682 records from SA Flora (BDBSA). 129435 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 9127 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 8871 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 12244 records from ULg_Hexapoda. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2295 records from Joint Nature Conservation Committee - England Otter Survey Database. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 346708 records from BioFokus. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 148166 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 184 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 35747 records from DMNS Bird Collection (Arctos). 78799 records from natagora-earlybirds. 3688 records from Clare Biological Records Centre dataset. 582 records from Bioblitz 2013 Copenhagen Denmark. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 25983 records from Monitoring data from the federal state Bavaria (Germany). 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 6330 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 34 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 11 records from Pollen profile from sediment core AV14_K2-4. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 33497 records from Dragonfly Ireland. 4202 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 34 records from Aschelminth collection of National Museum of Nature and Science. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 733 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 399 records from The Fish Collection at the Zoologische Staatssammlung München. 364997 records from University of Florida Vertebrate Paleontology. 80907 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 59 records from Im Bauerngarten. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 23003 records from Amphibian Specimens. 4498 records from Colección Herbario Universidad Católica de Oriente. 355 records from Culture Collection of Cryophilic Algae. 767 records from BioGIS - Bats - Asaf Tsoar database. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 8399 records from UAM Fish Collection (Arctos). 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 286414 records from Coordinated Waterbird Counts. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 11826 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 97 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 201 records from BioAcoustica: Wildlife Sounds Database. 34 records from Sipuncula collection of National Museum of Nature and Science. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 1364 records from Irish Collembola records. 236 records from GENT Lactarius Deliciosi. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 393 records from Danish Lacewings (Neuroptera). 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 2223 records from CESJ - Herbário Leopoldo Krieger. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 546 records from OUPR - Herbário "Professor José Badini". 1 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 13 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 464 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 567 records from Collection of Hymenoptera. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 2353 records from MISE Project Otter Records, 2011-2015. 43 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 895 records from Lichen.ie Data. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3372 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 133180 records from NINA insect database. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 2126 records from HAS-Algae - Coleção Ficológica do HAS. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 55 records from Molluscan fauna of Gueishan Island of Taiwan. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 24301 records from Tromsø Museum, Fungi. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 136 records from Plants galls. 99830 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 3842 records from CRCM Vertebrate Collection. 7416 records from The atlas of breeding birds in Małopolska. 461 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 14239 records from Cowan Tetrapod Collection - Mammals. 2282 records from Ohio University Invertebrate Paleontology Collection. 2136 records from Herbario Museo de La Salle Bogotá (MLS). 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 146 records from Megophthalmidia_of_North_America. 7203 records from Royal Horticultural Society - Records from the RHS insect reference collection. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 873 records from Kartlegging av spredning av fremmede bartrær. 5116 records from HAMAB - Herbário Amapaense. 10103 records from CUMV Mammal Collection (Arctos). 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 41 records from CIM Specimens. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 75981 records from Irish Vascular Plant Data - Paul Green. 260 records from SuLaMa reptile survey II 2012. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 3801039 records from FlorKart - FlorenKartierung Gefaesspflanzen. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 349121 records from Plantae of Costa Rica (INBio). 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 58 records from Mamíferos laguna El Tinije. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 7402 records from Helgeland Museum, Lepidoptera. 12824 records from CUMV Fish Collection (Arctos). 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 2 records from Counts of benthos communities in Kongsfjorden in 2009. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 1661 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 764 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 100305 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 34 records from Borkhart. 1764 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 25884 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 814416 records from Fauna Atlas N.T.. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 58 records from LISU Herbario Angola. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 53749 records from Field Museum of Natural History (Zoology) Bird Collection. 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 109641 records from UAM Mammal Collection (Arctos). 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 7 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 27 records from HSU Wildlife Eggs and Nests. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 41485685 records from Artdata. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 310 records from Lepidoptera collection, NTNU, Trondheim. 14371 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 858 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 3 records from MfN - Micropaleontology. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 509665 records from Museum Victoria provider for OZCAM. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 1742 records from Eggs Specimen. 35803 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 2 records from New genus of diminutive microhylid frogs from Papua New Guinea. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 2 records from CCBER Mammalogy Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 87 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 7348 records from Herbier du Bénin. 2593 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 9088 records from Flora of Słowiński National Park, Poland. 690 records from Odonata collection, NTNU, Trondheim. 1921 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 1335 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 21545 records from Butterflies of Ireland. 3 records from Diatom abundance of Hole 38-338, Part 2. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 71 records from (Data S1) Palynology of ODP Site 113-696. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 758 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1750 records from Flora of tanzania. 16192 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 12691 records from MBM - Herbário do Museu Botânico Municipal. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 1905 records from BioGIS - Reptiles - INPA database. 342 records from Kremmer Luch. 7 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 314 records from Peces laguna El Tinije. 10326 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 610 records from INRA-Versailles Arabidopsis natural variants. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 6698 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 2706 records from Alien macro-invertebrates in Flanders, Belgium. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 220 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 20 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 1287 records from Harvestmen_of_French_Guiana. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 2810 records from Helgeland Museum, Araneae. 4972 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 78804 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 3275824 records from Insecta of Costa Rica (INBio). 61613 records from Atlas of Iberian water beetles (ESACIB database). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 352 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 55002 records from Biological Records Centre - Reptiles and Amphibians Dataset. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 3712 records from Saproxylic Beetles of Ireland. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 10584 records from Danish Plant Bugs (Miridae). 28498 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 18643 records from Endemic plants of the Congo basin. 117 records from Various insect orders, NEF. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 27975 records from Inventaire National du Patrimoine Naturel : Loup en France. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 570893 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 880841 records from SA Fauna (BDBSA). 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 3800 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 810 records from Chrysomelidae of the Carpathians. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 3284 records from Algae (S). 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 127927 records from OHN. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 2 records from Ichthyologie ZMK. 199 records from MVZ Hildebrand Collection (Arctos). 51 records from Packer Collection / Xenochilicola bees, Chile. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 633712 records from Données ONF Faune-Flore-Fonge. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 5 records from FCAB - Herbário Friburguense. 27061 records from Bird Monitoring Data. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 1668 records from Fungus herbarium, UiB. 111036 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 71 records from HSU Wildlife Mammals. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 12002 records from Lund Museum of Zoology (MZLU). 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 163805 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 2 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 2 records from Echinodermata ZMK. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 965 records from Freshwater plants of Cameroon. 396127 records from British Lichen Society - BLS Lichen Database: English churchyards. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 271 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2070 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 200 records from Colección de Zoología Invertebrados - Otros invertebrados. 411 records from SuLaMa reptile survey I 2012. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 157666 records from Field Museum of Natural History (Zoology) Mammal Collection. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 71214 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 1 records from Ornithologie ZMK. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 9688 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 281 records from Myriapoda of Costa Rica (INBio). 1 records from Vermes ZMK. 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3218 records from Road Kill Survey. 1 records from Reptilia ZMK. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 495776 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 6 records from Malakologie ZMK. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 9006 records from Tallinn Botanic Garden. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 431 records from Upper Silesian Museum, Insect Collection. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 283 records from Crustacea ZMK. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 31962 records from Herbier de Nouvelle-Calédonie. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 69125 records from CAS Invertebrate Zoology (IZ). 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 4240 records from Crustacea collection of National Museum of Nature and Science. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 83669 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 614 records from UCM Bird Eggs/Nests Collection (Arctos). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 6518 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 9 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 60 records from Shrews of Poland. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 200 records from Zoological collection of the National Museum. 3620 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 2742 records from Plant (KIWE-PL). 5561 records from IWDG Casual Cetacean Sightings. 4 records from Culture Collection of Algae. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 144 records from Annelida collection of National Museum of Nature and Science. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 15 records from Tardigrada collection of National Museum of Nature and Science. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1000 records from Colección Limnológica del Chocó. 19084 records from UAM Bird Collection (Arctos). 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 7 records from (Table 4) New palynological record of sediments from Odderade. 10501 records from Naturalis Biodiversity Center (NL) - Cnidaria. 117 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 749207 records from Historical Bird Atlas. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 8716 records from CHAS Mammalogy Collection (Arctos). 15843 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1054815 records from Norwegian Biodiversity Information Centre - Other datasets. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 3406 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 240 records from MPM Herpetology. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 59 records from CCBER Ornithology Collection. 2952 records from Geneva Herbarium – Burnat Herbarium (G-BU). 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 688 records from Algae, Norwegian College of Fishery Science. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 1150 records from arim. 9187 records from Herbarium of the Université Libre de Bruxelles. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 37 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 135412 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 21868 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 259583 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 5311 records from Natural History Museum Maastricht (NL) - Herbarium. 169 records from The Pteridaceae family diversity in Togo. 5790 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 12 records from Naturalis Biodiversity Center (NL) - Mammalia. 1025 records from tef-database. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 4858721 records from Australia's Virtual Herbarium. 35445 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 443 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 35266 records from Kathryn Kalmbach Herbarium. 162218 records from Ichthyology Collection - Royal Ontario Museum. 1571 records from Banco de Germoplasma del Jardín Botánico Atlántico. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 4817104 records from Bird Ringing Centre in Sweden (NRM). 49637 records from Monitoring data from the federal state Hesse (Germany). 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 4452 records from Invertebrate collection of University of Oulu Zoological Museum. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 2760 records from ESAS cetacean sightings from 1980 to 2003.. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 7551382 records from BirdLife Australia, Birdata. 748178 records from Museum of Comparative Zoology, Harvard University. 2080 records from Naturalis National Natural History Museum (NL) – Coelenterata. 291657 records from SEAPOP NINA. 5 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 589 records from Birds (NMNO-BI). 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 1656346 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 13324 records from Collection of various insect orders, Natural History Museum, University of Oslo. 697 records from Herbier de Strasbourg. 56431 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1098 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 51401 records from Vascular Plant Herbarium, UiB. 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 3375 records from NMMNH Mammal. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 431 records from Plantas Bosque Seco Chicamocha. 9948 records from Bees of Canada / Gschwendtner property collection. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 17 records from Hazel Dormouse in Ireland. 12502 records from The Bat Conservation Trust - Hibernation Survey. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 1294 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 118931 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 65 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 163 records from Entomofauna laguna El Tinije. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 6004 records from Colección Limnológica Universidad de Antioquia. 65463 records from CAS Ornithology (ORN). 561 records from Líquens d'Andorra. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 16504 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 161 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1380439 records from Consortium of California Herbaria. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 9741 records from Finnish Entomological Database: Hymenoptera. 7470 records from National Taiwan University. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 2262 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 5 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 613 records from Countryside Council for Wales - Shad Monitoring data. 271 records from Beweidungsprojekt an der Nesse. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 74 records from SuLaMa reptile monitoring. 210614012 records from EOD - eBird Observation Dataset. 796 records from Biological Records Centre - Irish Otter Dataset. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 44590 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 8014 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 5506 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 2 records from Neue Milbenarten aus Kärnten. 14118 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 61 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 780 records from UCBG TAPIR Provider. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 16163 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 23 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 83531 records from UCJEPS TAPIR Provider. 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 2749 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 84521 records from BioGIS - Vascular plants - INPA database. 1443 records from Odonata of the Congo River 2010 expedition. 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 251763 records from Moths Ireland. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 3002 records from Colección de Peces Universidad Católica de Oriente. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 921969 records from iNaturalist Research-grade Observations. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 3669 records from ARKO strandeng. 2824 records from HUCS - Herbário da Universidade de Caxias do Sul. 34 records from National System of Protected Areas in Poland - Fungi. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 46 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 20893 records from H.A. Stephens Herbarium. 3 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 3214 records from Upper Silesian Museum, Bird Observations. 8399 records from NYSM Birds. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 100 records from Birdrace-Meister_der_Herzen-Kleve. 114 records from Flora. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 40460 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 557853 records from Aranzadi Ringing Scheme (bird ring-recovery data). 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 1077 records from BioGIS - Fish - HUJ collections. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 2877 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 47767 records from National Bat Database of Ireland. 3541 records from Coleção de Polychaeta do Museu Nacional. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 96 records from Birdrace-federleser-Herford. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 3225 records from Aquatic Oligochaeta of Ireland. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 155953 records from CONN. 914 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 56 records from UCM Vertebrate Observations Collection (Arctos). 1 records from A new ant genus from the southwestern United States.. 40036 records from Recent Invertebrates Specimens. 13720 records from Hemipteran specimens of Iwate Prefectural Museum. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 50000 records from observe_tuna_bycatch_ecoscope. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 10862 records from Heteroptera of Ireland. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 2201 records from UFRN-Fungos - Herbário UFRN - Fungos. 17 records from Spiders_of_French_Guiana. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 31 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 19 records from Flora of Japan Specimen Database. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 6309 records from University of Lethbridge Herbarium (LEA). 181 records from Alien Species in Poland - Animals. 13701 records from AM: Terrestrial Insect Collections (1896-2000). 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 1020 records from National Museum Of Marine Science & Technology. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 3330 records from Collection botanique Le Grand A. (BOUM). 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 1321 records from Herbier National de Mauritanie (HNM). 2775 records from Bolivian Amazon lowland fish metacommunity data. 92 records from Birdrace-Team_BO-bachter-Bochum. 65 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 6823 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 9338 records from KUBI Ichthyology Tissue Collection. 11615 records from Louisiana State University Herbarium - Vascular Plants. 45761 records from Estonian Museum of Natural History. 5 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 2 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 14095 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 3 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 22029 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 128739 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 96687 records from Invertebrates Collection of the Swedish Museum of Natural History. 1894 records from Fungi Collection. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 33173 records from Global Lacustrine Diatoms. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 11 records from Pollen profile from sediment core AV14_K2-1. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 86277 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 103 records from Birdrace-Die_Nachtigallen-Herford. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 17909 records from University of California Museum of Paleontology. 202161 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 8529 records from NINA botanical collection. 257 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 38393 records from Mammals housed at MHNG, Geneva. 3628 records from Wildbook for Whale Sharks. 1244 records from Mosquitoes_of_French_Guiana. 9598 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 60345 records from ALCB - Herbário Alexandre Leal Costa. 56 records from Onychophora of Costa Rica (INBio). 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 2121 records from HUSC - Herbário Unisanta. 23215 records from rmca-albertine-rift-butterflies. 14449 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 238553 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 21 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 104293 records from mel. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 118668 records from Estonian University of Life Sciences. 80 records from Förderzentrum Schmölln. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 419508 records from Meadow and Pasture Inventory (SJV). 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 1001 records from Circumpolar Seabird Monitoring Plan. 435 records from DMNS Marine Invertebrate Collection (Arctos). 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 9490 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 1472 records from Herbarium Rhoenmuseum Fladungen. 8441 records from Natural England - Batsites inventory for England. 176730 records from Essig Museum of Entomology. 23128 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 97 records from LauWi. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 13298 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 189 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 1658810 records from NMNH occurrence DwC-A. 15219 records from Census of the animals of Benin. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 68 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 15926 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 1116 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 10 records from Redescription of the little-known grasshopper Willemsella (Acrididae, Hemiacridinae) from Peninsular Malaysia. 12738 records from DMNS Mammal Collection (Arctos). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 170213 records from CAS Ichthyology (ICH). 40 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 1826 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 3327 records from BioGIS - Mammals - SPNI. 17435 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 1294 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 22029 records from TNHC Ichthyology Collection. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 13600 records from Mammal collection, Natural History Museum, University of Oslo. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 114 records from Birdrace-Finkenspötter-München. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 1658 records from MISE Project Waterford Otter Records, 2011-2015. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 24211 records from Monitoring data from the federal state Saxony (Germany). 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 120 records from Birdrace-Kosmos_Racer-Freising. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 112 records from Birdrace_Die_Borner-Viersen. 110 records from Birdrace-LiLaMai-Vechta. 109 records from Birdrace-Team_Charadrius-Günzburg. 105 records from Birdrace-ARKONAuten-Rügen. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 95 records from Birdrace-Buteo1_DO-Dortmund. 91 records from Birdrace-Enger_am_Spektiv-Herford. 72 records from Birdrace-Buteo2DO-Dortmund. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 76 records from Birdrace-Birding_for_Nature-Bonn. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 128 records from Birdrace-Brut-Wetteraukreis. 746 records from Literature based species occurrence data of birds of North-East India. 111 records from Birdrace-Uhulogen-Lippe. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 113 records from Hochschulgelände (Bremen). 37 records from Berlin - Treptower Park / Karpfenteich. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 6072 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 41 records from Örtzemündung (Stedden). 10 records from Kita-Wäldchen Fuchsturmweg Jena. 106 records from Schulgarten Hans-Carossa-Oberschule. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 99 records from Düne am Ulvenberg (Darmstadt). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 111 records from Ökologischer Weinberg (Guntersblum). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 65 records from Mauernacker (Wettsaasen). 17 records from Schutzgebiet Ochtersum. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 40 records from Flächennaturdenkmal Grubditz. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 214 records from Binsenwiesen. 101 records from Isartal Dingolfing. 172 records from Leben im Finkensteiner Moor. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 108 records from Birdrace-TriumVIErat-Viersen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 101 records from Birdrace-Herford-Birder-Herford. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 85 records from Birdrace-Die_Paradiesvögel-Herford. 127 records from Birdrace_Schräge_Vögel-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 360 records from Küstenschutzwald. 100 records from Feriendorf Ober-Seemen. 50274 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 100 records from Grenzturm Hohen Neuendorf. 70 records from Lech 2001. 52 records from Fledermaus. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 57 records from Heidesee / Halle. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 29 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 101 records from Naturgrundstück (Eutin). 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 233 records from Föhrenried (Fronreute und Baindt). 263 records from Artenvielfalt Kreis Gießen. 282 records from Deponie Klausdorf. 20 records from Motzener Tonsee. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 45 records from Flusswerder in der Weser (Hameln). 66 records from Wedeler Au. 150 records from Steinbruch Mainz-Weisenau. 54 records from Wiese am Unterbecken. 95 records from Ortelsbruch - Hangmoor bei Morbach. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 219 records from Umgebung der Grundschule Oderberg. 161 records from Schussenaue bei Berg. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 85 records from Insektenvielfalt Ahe/Weichelsee. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 185 records from Klasse 3a. 342 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 241 records from BIRDRACE RennVögel Münsterland. 257 records from Seewasen. 162 records from Siegen/ Gymnasium Am Löhrtor. 198 records from FNL e.V.. 83 records from Spechtwald. 122 records from Kloster Eberbach. 151 records from Isarufer. 44 records from "Schlechteberg" Ebersbach/Sa.. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 245 records from Kiesgruben Wemb. 84 records from Roter Berg Werdau (Leubnitz). 57 records from Waldhusener Moor (Lübeck-Kücknitz). 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 23 records from Alter Nördlicher Friedhof (München). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 39 records from Südpark (Bochum-Wattenscheid). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 64 records from Kabelskebach (Kabelsketal, Saalkreis). 96 records from Die Wuhle. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 180 records from Paul-Gerhardt-Schule Dassel. 86 records from Alter Kreidebruch Saßnitz/Rügen. 113 records from Rund um das LUGY. 31 records from Nationalpark Harz Schul-AG Braunlage. 107 records from Landschaftsschutzgebiet Buchhorst 3. 122 records from Stever. 12 records from Kindergarten. 9 records from Willersalpe. 108 records from Mainufer. 59 records from Rund ums Ökohaus (Würzburg). 32 records from Schulhof Sandhofenschule (Mannheim). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 69 records from Lassentiner Moor (Niepars). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 69 records from Schulgarten mit Klasse 8a (Essen). 97 records from Döchtbühlwald (Bad Waldsee). 15 records from AKG-Bensheim. 270 records from Regenrückhaltebecken (Zeulenroda). 313 records from Stadtpark Herzberg (Elster). 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 167 records from Zielbach (Töll). 170 records from Bodenseeufer Radolfzell. 56 records from Zitadelle Berlin-Spandau (7b). 325 records from Triebesbach (Zeulenroda-Triebes). 22 records from Dellwiger Bach (Dortmund). 46 records from Hainbachtal in Oelsnitz/V.. 308 records from Wangerooge. 101 records from Naturhausgarten. 58491 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 149 records from Wirbach. 145 records from privater Garten. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 50 records from Junge Heide, Radebeul/Dresden. 54 records from Ludwigshofen. 18 records from Spielwiese. 117 records from Wassermann. 54 records from Zentralfriedhof (Wien). 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 73 records from Varnhalt. 79 records from Balkon (Norderstedt). 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 103 records from Wasserwerkspark (Chemnitz). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 103 records from Schwanseepark (87645 Schwangau). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 99 records from Dorfrand Mauderode. 110 records from Obstwiese Osterberg. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 133 records from Wulfsmuehle/Pinnau. 124 records from Wiesenbiotop am Wasserturm. 212 records from Artenvielfalt im Beckerbruch (Dessau). 28 records from Sandgrube Zaisertshofen. 160 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Trockenrasen bei Dörndorf. 1035 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 77 records from Trockenrasen Franzigmark (Halle/Saale). 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 22 records from Heilpflanzen im Hainbachtal. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 98 records from Warnowtal (Rostock). 19 records from Goethe-Hauptschule/Projekt I-10. 153 records from Selztal bei Friesenheim. 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 28 records from Uferzone Wipper (Biesenrode). 22 records from Breitkopfbecken (Berlin-Reinickendorf). 139 records from NSG Leist bei Ziegenhain. 62 records from Amtsrain Apolda-Zottelstedt. 61 records from Artenvielfalt auf der Wiese. 43 records from Saalewiesen Naumburg. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 60 records from Schafsweide Seniorenhaus Berghof. 53 records from Weidegut Rechab. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 58 records from Weidewirtschaft. 94 records from Kochertgraben II. 63 records from Hochschule Zittau/Görlitz. 61 records from GE-Brühl. 107 records from vegoek. 46 records from Neanderthal. 86 records from Naturerlebnisraum Koppelsberg (Plön). 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 60 records from NABUGEO1. 69 records from Entdeckertour am Muldestausee 1/05. 155 records from Birdrace-Usedommeln-Ostvorpommern. 128 records from Birdrace_turbine_untersee-Konstanz. 181 records from Spießwoogtal / Königsbruch (Fischbach). 35 records from Urwald 3 (Bad Waldsee). 5 records from Streuobstwiese (Mittelgasse 4). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 244 records from WildesMoor bei Schwabstedt. 92 records from Birkenloh. 172 records from Dalbekschlucht. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 54 records from Weidegebiete in der Selzrenaturierung. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 97 records from Landschaftspark St.Leonhard-Deisendorf. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 42 records from sbosch. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 23 records from Wiese Niederaula. 89 records from Birdrace-Team_Wangerooge-Friesland. 62 records from Zoo Frankfurt. 57 records from Schulgarten Fichteschule. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 142 records from Kinderbauernhof Pinke-Panke. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 21 records from Bach. 31768 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 29 records from Naturerfahrung. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 40 records from Schulhof Liebfrauenschule Oldenburg. 51 records from Schrebergarten Düsseldorf Oberkassel. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 64 records from Schafheide im Böblinger Wald. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 26 records from Erhard Sopp. 16487 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 50 records from Artensuche auf den Elbwiesen in Radebeul. 59 records from Oschenberg, NO von Bayreuth-Laineck. 4 records from Schulbiotop und Brigach (Villingen). 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 245 records from Gieselbachtal Fulda-Harmerz. 43 records from Schulgelände Thurmair-Gymnasium. 28 records from Hainbachtal bei Oelsnitz / V.. 55 records from Flora und Fauna am Mittelrheintal. 95 records from Vielfalt verschiedener Wiesen. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 155 records from Bammentaler Duft- und Heilkräutergarten. 147 records from NABU-Auerochsenweide. 748 records from Moluscos Marinhos de Augusto Nobre. 93 records from Höltigbaum. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 98 records from Rund ums Cani. 15 records from Regenwasserabfangsbecken (Erlenbach). 193 records from Gelände des Schulzentrums am Himmelsbarg. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 207 records from Biosphäre Bliesgau. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 134 records from Birdrace-Team_Havelland-Havelland. 9866 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 100 records from Birdrace-The_Ringers-Friesland. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 10 records from Feuchtwiesen Wippertal bei Wippra. 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 13 records from Garten Hamburg Uhlenhorst. 41 records from Morphologische Daten von Natrix. 221 records from Römertal (Steinpleis). 78 records from Birdrace-Die_Laufenten-Braunschweig. 51 records from Steinbachtal (Würzburg). 81 records from Stadtpark Schmölln. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 10 records from Ökowerk Emden. 21 records from Tauchen und Meer 02. 84 records from Streuobstwiese Haus Zeitz. 22 records from Bachabschnitt der Nette (Osnabrück). 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1174 records from Sudeniederung (Amt Neuhaus). 23 records from Ackerrain Plönhagen. 24 records from Kaisertal. 10 records from schlittschuhweiher. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 13 records from FND "Weißer Berg" Leißling. 5 records from Feuchtwiese. 21 records from LBV-Kindergruppen Markt Tussenhausen. 34 records from Wattenmeer-Safari (Wurster Watt). 6 records from Sächsische Schweiz (Pfaffenstein). 149 records from BIRDRACE Birding Bentheim. 126 records from BIRDRACE Duckehühnchen. 80 records from Feldweg Waldkirchen. 132 records from Aachtobel. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 85 records from Ober-Olmer Wald. 66 records from Von der Nutzung zur Natur. 49 records from VFD-H.: Rheingau: Bärstadt. 36 records from Liether Park 1 (LMS), Klasse 5b. 83 records from BIRDRACE Die Frankenpfeifer. 177 records from BIRDRACE Mehr Seh Team. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 114 records from BIRDRACE LiLaLau. 69 records from Unter hellen Zinnen und finsteren Grotten. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 39 records from Soolbach-Tal. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 122 records from Birdrace-Hügelland-Mainz/Bingen. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 79 records from Birdrace-Bielefinken-Bielefeld. 2913 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 46 records from 8c. 63 records from Sternwiese Mülheim-Broich. 21 records from Riedkanal Bötzingen. 71 records from Birdrace-do_elster_Dortmund. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 54 records from Park Schönfeld (Kassel). 64 records from Pilzlehrwald. 117 records from Naturschutzgebiet Kochertgraben. 35 records from Gym Freyung. 101 records from Hoher Stein Kallenhardt. 141 records from Draubiotop Lavamünd. 11 records from Waldgebiet Todtnau- Sonnhalde. 57 records from Mauervegetation,Flechten und anderes. 26 records from Schulteich Heinrich-Mann-Schule. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 27 records from Zwickau- Schwanenteich. 32 records from Nationalpark Harz Juniorranger. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 8 records from Streuobstwiese. 29 records from Brenz (Heidenheim). 36 records from Olympiapark (München). 15 records from Beisetal bei Niederbeisheim. 27 records from Wiese hinter der Schule (Darmstadt). 20 records from Mikroorganismen. 15 records from Bodentiere rund um die Schule. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 29 records from Insekten. 36 records from Salzwiese Diekskiel. 3 records from FFR Hausen. 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 8 records from Krittenhorster Wald (Ostkilver). 107 records from Müritz-Nationalpark. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 53 records from Bad Bodenteicher Heide. 102 records from Industriebrache (Kempen). 31 records from Kurler Busch (Scharnhorst). 4 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 36 records from Selz (Ingelheim am Rhein). 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 39 records from Stausee Weiditz. 65 records from LSG "Großes Bruch". 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 81 records from Birdrace-Die_Ornithomaten-Herford. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 87 records from Klütwald. 57 records from Garten in Schmölln. 36 records from Plöwener Wald. 49 records from Dörnberg. 47 records from Schulgelände Ceciliengymnasium. 31 records from Regenwasserabfangbecken. 4334 records from MVZ Bird Observations (Arctos). 39 records from Regenrückhaltebecken Bad Bevensen. 27 records from Vögel. 13 records from Tiere im Teichgebiet. 81 records from Schulgarten-St.-Georg-Gymnasium. 56 records from Estetal (Buxtehude). 64 records from Issumer Fleuth. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 23 records from AKG-Gelände in Bensheim. 19 records from Glemstal (Leonberg). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 24 records from Ornithologische Wanderung um Tussenhausen. 48 records from Heider Bergsee (Brühl). 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 22 records from Kaltenkirchen Brache. 51 records from Mühlenbach bei Buxtehude. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 20 records from Lerchenauer Baggersee (München). 80 records from Lahnufer in Villmar. 28 records from Stadtpark Prinzengarten (Sigmaringen). 23 records from Tümpel Schulbiologiezentrum. 12 records from Kinderwald Hannover. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 611 records from IBF Monitoring of Plant Galls. 6 records from Fließgewässeruntersuchung am Haselbach. 45 records from Georgs-Padd (Wangerooge). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 13 records from Warnowufer Groß Klein. 1 records from Graureiher in Lans. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 11 records from Privatteich(St.Leon). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 40 records from Tiere und Pflanzen um uns herum !. 27 records from Bäche im Mooswald (Vörstetten). 17 records from Kohlbach (Sulzfeld). 18 records from Naturtag. 10 records from Bachpatenschaft Beeke. 4 records from Sächsische Schweiz (Wehlener Gebiet). 15 records from Tiere. 94 records from Landschaftsschutzgebiet Buchhorst 4. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 7 records from Stadtrandlandschaft Apolda-Nord. 5 records from Schulinnenhöfe (Gelsenkirchen). 11 records from Vögel im Garten Kindergarten Zaisertshofen. 12 records from Schulgelände Erich-Kästner-Schule. 3 records from Blankenfelder See. 6 records from Boimstorfer Sundern. 1 records from Fledermäuse über der Alster (Hamburg). 119 records from BIRDRACE Tick, Trick und Track. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 9 records from Wiesendreieck Luckenwalde. 16 records from Im und um das Schulhaus. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 59 records from Schulteich Freie Waldorfschule Darmstadt. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 1 records from Waldtag in und um Seelingstädt. 2 records from Hildener Heide - Spörkelnbruch (Haan). 1 records from Karpfenteich, Klasse 6d. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 401823 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 15518 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 36245 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 1095 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 555 records from FFH-Gebiet "Calwer Heckengäu". 80 records from Landschaftsschutzgebiet Schmutterwald. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 371 records from Bannwald Burghauser Forst. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 23 records from Wattuntersuchung (Cuxhaven). 17 records from Tierpark Zittau. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 24 records from Tauchen und Meer. 15 records from Kirchheller Heide ( Bottrop). 12 records from Ohemoor (Hamburg/Norderstedt). 15 records from Urwald 2 (Bad Waldsee). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 135 records from Waldi-Weiher. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from 5. Wiener Gemeindebezirk. 5 records from Fledermäuse u. nachtaktive Insekten. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 1424 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 88956 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 89 records from Schulgelände Paul-Gerhardt-Schule. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 52 records from Naturschutzstation Weinberghaus (Dessau). 112 records from Kaniswall/ Gosener Wiesen an der Spree. 517 records from Schulzentrum "Parc Hosingen". 274 records from Bernhardsthal. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 126 records from Schulwald Marksuhl. 313 records from BIRDRACE Gätkes Erben. 369 records from BIRDRACE Havelland. 269 records from BIRDRACE Kosmos-Racer. 145 records from BIRDRACE Dith Marsh Sandpiper. 115 records from BIRDRACE Die UHULOGEN. 24098 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 508 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Tag der Artenvielfalt am Bruckenwasen. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 61 records from Fürstenberger Ralley Teil 3. 15 records from Kühnauer Aue und Kühnauer See. 359 records from Pöhlberg bei Annaberg. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 93 records from Haarbach Höfe. 74 records from Schulwald Grundschule Brügge. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 278 records from BIRDRACE Usedommeln. 279 records from BIRDRACE Wannacks Topti(c)ker. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 256 records from BIRDRACE Upupa epöpse. 65 records from BIRDRACE Federal Birds of Investigation FBI. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 118 records from BIRDRACE Die Lippegeier. 78 records from BIRDRACE leucorhö statt logorrhö. 84 records from BIRDRACE Bielefinken. 91 records from BIRDRACE SchrägeVögel. 96 records from BIRDRACE Emslandracer. 158193 records from All Ireland Non-Marine Molluscan Database. 134 records from BIRDRACE Griffin Wood Warblers. 132 records from BIRDRACE Die Wetterauer. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 114 records from BIRDRACE VIE will rock you!. 112 records from BIRDRACE Gütersloher Gimpel. 112 records from BIRDRACE Hügelland zu Fuß. 111 records from BIRDRACE Die Wendehälse. 109 records from BIRDRACE Die Borner. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 194 records from Bodenteicher Seewiesen. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 169 records from Expedition "Schulgelände". 1176 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 146 records from LK 11 im Mönchspark. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 366 records from Weinberg Reichersdorf. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 161 records from BIRDRACE Nord-Seh-Team. 272 records from BIRDRACE Niederlausitz-Team. 274 records from BIRDRACE Asiola-Quartett. 254 records from BIRDRACE Thüringer Becken-Birders. 258 records from BIRDRACE Raumpatrouille Oriolus. 69 records from BIRDRACE Pfeifenten. 140 records from BIRDRACE Guckers Offenbach. 157 records from BIRDRACE Rheinische Wasserrallen. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 80 records from BIRDRACE Falkenberger Fluppis. 82 records from BIRDRACE Die Ziegeneier. 84 records from BIRDRACE Avinauten. 166 records from BIRDRACE Die Düsselmöwen. 95 records from BIRDRACE BiBi. 95 records from BIRDRACE accipiter hardcore birding. 97 records from BIRDRACE NABUhu Trier!. 98 records from BIRDRACE Die Paradiesvögel. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 100 records from BIRDRACE Stuttgart 100 trööt. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 102 records from BIRDRACE Buteo1DO. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 103 records from BIRDRACE federleser. 103 records from BIRDRACE Die Otzberger. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 104 records from BIRDRACE Erlanger Piepmätzchen. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 105 records from BIRDRACE coesfelder_vogelkundler. 174 records from BIRDRACE Bon(n)apartemöwen. 106 records from BIRDRACE Ave Goettingen!. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 144 records from BIRDRACE Die Mohrenlerchen. 287 records from BIRDRACE Pody und Co. 138 records from BIRDRACE Arkonauten. 82 records from BIRDRACE Buteo2DO. 91 records from BIRDRACE NABU LV Hessen. 96 records from BIRDRACE OAG Neuwerk. 99 records from BIRDRACE TEAM BO-BACHTER. 101 records from BIRDRACE Enger am Spektiv. 102 records from BIRDRACE Willi goes Birding. 102 records from BIRDRACE Westfälische Nachtigallen. 105 records from BIRDRACE Kiesmätze. 131 records from BIRDRACE Brut. 120 records from BIRDRACE The early birds. 58771 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 114 records from BIRDRACE Di-Bi-Di-Birder. 110 records from BIRDRACE Angeliter Ornis. 121 records from BIRDRACE Immerwiederhopf. 108 records from BIRDRACE Diesmal sehen wir mehr. 107 records from BIRDRACE Herford Birders. 107 records from BIRDRACE Borussia Zippammer. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 44 records from Wiesen am Treffpunkt Freizeit. 67 records from Tongrube bei Hettstedt. 145 records from Gronau - auf der Suche nach dem Neunauge. 37 records from Liether Park 2 (LMS), Klasse 6c. 504 records from Schatzinsel Wangerooge. 144 records from Lustbach-Umland. 121 records from Owere Fiddel. 62 records from Hettstadt Gehäge. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 113 records from Tornoer Teich. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from VFD-H: MIttelgebirgsweide. 99 records from Streuobstwiese Stedar. 114 records from Liether Kalkgrube. 101 records from Steinbruch Kronungen. 85 records from Rund um den Hainbergsee. 54 records from Wir erkunden die Hofau, Klasse 5c. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 61 records from BIRDRACE Baumläufer. 79 records from BIRDRACE Blinde Hühner. 90 records from BIRDRACE TicTacToe. 106 records from BIRDRACE Die Schwenker-Birder. 101 records from BIRDRACE nabu-rhein-main.de. 402 records from Tag der Artenvielfalt in Heidelberg. 2212 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 173 records from FFH-Gebiet Klosterwasser/Burkau. 66 records from Langes Tannen(LMS), Klasse 5d. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 54 records from Biotope im Schulumfeld. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 62 records from Lebensraum Dorf. 248 records from Schulgarten der Volksschule. 116 records from Sürther Aue. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 61 records from Wälder im Hainbachtal. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 96 records from "Ahrschleife bei Altenahr". 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 269 records from BIRDRACE speedbirder. 269 records from BIRDRACE Dithmarscher Deichhühner. 84 records from BIRDRACE Birding for Nature. 88 records from BIRDRACE Kingfisher. 143 records from BIRDRACE Die Laufenten. 120 records from BIRDRACE Ornis im Einsatz. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 69 records from BIRDRACE Mathilden-Käuze. 84 records from BIRDRACE Vogelscheuchen. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 152 records from BIRDRACE NAJU-Aspach. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 2483 records from NX - Herbário Nova Xavantina. 63 records from Rosarium (LMS), Klasse 6a. 30 records from Leben auf einer Sturmfläche. 45 records from Reusaer Wald. 18 records from Schulgarten der Gesamtschule Am Heidberg. 58 records from Schulgarten Zinnowwald-GS. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 214 records from Pflanzen und Tiere im Burgwald. 29 records from Waldwiese. 76 records from BIRDRACE Nachtigallen. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 68 records from IBF Monitoring of Orthoptera. 18 records from Landschaftsschutzgebiet Buchhorst2. 30 records from Geführte Wanderung im Eselsbachtal. 75 records from BIRDRACE Die Kartoffelsäcke. 31 records from Düpenauwiesen. 48 records from Wahner Heide LK 12 Biologie. 52 records from Aktion der Klasse H2 in Simmelsberg. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 146 records from BIRDRACE VdW Wilder Westen. 38 records from Was lebt in der Brutzwiese?. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 7 records from Die Bachspezies. 51 records from Kindervilla Außengelände. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 102 records from BIRDRACE Niederrheinische Bartgeier. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 104 records from BIRDRACE Andechser Stativträger. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 176 records from BIRDRACE Professorenteam. 277 records from Colección de Entomología - Auchenorrhyncha. 110 records from BIRDRACE Linumer Luchschleicher. 120 records from BIRDRACE Die TUErteltauben. 27 records from Schulgarten Waldorfschule Hassfurt. 94 records from FFH-Gebiet Paartal. 47 records from Schulgelände Grolland. 57 records from Schulgarten Janusz-Korczak-Realschule. 1964 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 17 records from Bachrenaturierung Littfe. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 40 records from BUND Naturschutzzentrum St. Julian. 12 records from Art´n Vielfalt im Kinderwald. 7685 records from European riparian ground beetles. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 30 records from Höhle am Neuweg / Sächsische Schweiz. 1 records from Streuobstwiese Alt Necheln. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 5477 records from Colección de mamíferos de la Universidad del Valle. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 1077 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 75 records from Naturpark Kottenforst-Ville 19.6.09. 6325 records from Colección Entomológica de la Universidad de Antioquia. 53 records from BIRDRACE Taubenhaucher. 33 records from Schüler erforschen die Helme-Aue. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 17 records from Nachtinsekten am Muldenufer. 192 records from "Schwarzwassertal" bei Pobershau. 61 records from (Table 1) Sedimentology of core D11957P. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 75 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 33 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, 63-125 µm fraction. 2833 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 50 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 12 records from Flora und Fauna am Mühlberg. 77 records from VFD-RP: Taunus: Mähweide Dehe. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 563 records from NRM-Herpetology. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 3492 records from Species counts of benthic foraminifera of sediment core BOFS5K. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 10 records from Monitoring of Nigritella nigra in the Kvikne mountains, Tynset, Norway. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 41 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, >125 µm fraction. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 273 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core GIK17728-1 (Table 4). 837 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 128 records from Benthic foraminifera assemblage in sediment core BBLL2_MC4. 48 records from Assemblage of living benthic foraminifera in sediment profile GeoB4901-6. 108159 records from CSIRO, Marine Data Warehouse Biology Records Pre-1998, Australia, 1978-1997. 41 records from Liether Park (LMS), 6c. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 85 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 30-63 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 45 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 684 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 68 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 129 records from Abundance of living benthic foraminifera in sediment core CD86_01_BC1. 92 records from Total foraminifera counts from multinet SO119_MSN1295. 349 records from Benthic foraminiferal assemblage in the 125-250 micron fraction of sediment core PS1745-5 (Table 5). 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 169 records from Benthic foraminifera assemblage in sediment core BBLL2_MC1. 335 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 733 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 549 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 482 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 24 records from Liether Park (LMS), 6b. 212 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 124 records from Benthic foraminifera assemblage in sediment core BBLL3_MC2. 108 records from Assemblage of living benthic foraminifera in sediment profile GeoB4906-5. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 663 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 253 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 553 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 286 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 66 records from Abundance of living benthic foraminifera in sediment core CD86_03_BC4. 149 records from Schiller Gymnasium Hof 10b. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 216 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 2 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 329 records from Benthic foraminifera counts of sediment core GIK23351-1. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 530 records from Benthic foraminifera counts of sediment core GIK23352-3. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) counts of benthic foraminifera, SE France. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) benthic foraminifera. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 242 records from Schieferbrüche. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 945 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23414-9 in the Norwegian Sea. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 790 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_100MC. 412 records from Benthic foraminifera counts of sediment core GIK23063-3. 432 records from Benthic foraminifera counts of sediment core PS1246-4 (GIK23246-4). 656 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_107MC. 376 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 874 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_98MC. 477 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 637 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1550 records from Species counts of benthic foraminifera of sediment core BOFS14K. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 116 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 313 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction >150 µm. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 69 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 131 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 142 records from Assemblage of living benthic foraminifera in sediment core GeoB4904-7. 76 records from Faunal assemblage of sediment core GS7603-8. 734 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 14 records from Abundance of Globorotalia menardii of sediment core GeoB2110-3. 5 records from Plasm bearing foraminifera counts from multinet M31/2_MSN887. 289 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 1242 records from Lower Albian Moriez core (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 745 records from Counts of the dead benthic foraminifera assemblage in surface sediments of the North Atlantic. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 118 records from Abundance of dead benthic foraminifera in sediment core CD86_03_BC4. 38 records from Abundance of dead benthic foraminifera in sediment core CD86_07_BC4. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 62 records from Abundance of living benthic foraminifera in sediment core CD86_10_BC4. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction 63-150 µm. 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 144 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction 63-150 µm. 274 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction >150 µm. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 41 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC469. 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 43968 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 203793 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 57 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction 63-150 µm. 2210 records from Merseyside BioBank - North Merseyside Mammals (unverified). 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 7 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 30-63 µm fraction. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, >150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 13737 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 227 records from Total foraminifera counts from multinet M31/3_MSN916. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 345 records from Diversity of benthic foraminiferal faunas and benthic foraminifera accumulation rates of ODP Site 184-1143. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 31 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction >150 µm. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 228 records from Total foraminifera counts from multinet M31/3_MSN917. 4 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 30-63 µm fraction. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 28 records from Counts of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 248 records from Counts of Quaternary foraminifera of sediment core CRP-1 (App. 1). 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 65 records from (Table 4b) Downcore distribution of live benthic foraminifera of sediment core SW_3b, California continental borderland. 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 69 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, 63-150 µm. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, 63-150 µm. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 110 records from Artenvielfalt und Kulturlandschaft. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 569 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 148 records from Faunal assemblage of sediment core GS7603-11. 75 records from Faunal assemblage of sediment core TR149-32. 891 records from Benthic foraminifera accumulation rate of sediment core MD01-2378 during marine isotope stage 3. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 66 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 915 records from (Appendix Table 2) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 269 records from Distribution of planktic foraminifera of sediment trap NB6. 131 records from Total foraminifera counts from multinet M31/2_MSN887. 121 records from Total foraminifera counts from multinet M31/2_MSN893. 227 records from Total foraminifera counts from multinet M31/3_MSN918. 233 records from Total foraminifera counts from multinet M32/5_MSN976. 149 records from Total foraminifera counts of multinet SO117_MSN1243. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 134 records from Number of dead benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 67 records from Number of live benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 516 records from (Appendix B1) Calcareous nannofossils of ODP Site 208-1262. 129 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 166 records from Assemblage of living benthic foraminifera in sediment core GeoB3725-1. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB4912-4. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 89 records from Assemblage of living benthic foraminifera in sediment core GeoB4918-4. 588 records from (Table 5) Foraminiferal numbers of empty test of important species in surface sediments. 76 records from Faunal assemblage of sediment core GS7603-10. 77 records from Faunal assemblage of sediment core GS7603-12. 73 records from Faunal assemblage of sediment core GS7603-13. 75 records from Faunal assemblage of sediment core GS7603-9. 72 records from Faunal assemblage of sediment core TR149-35. 347 records from (Table 4) Standing stock values of important species in surface sediments. 70 records from Faunal assemblage of sediment core GS7603-14. 152 records from Faunal assemblage of sediment core TR149-38b. 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 2464 records from Benthic foraminiferal abundances at the Cretaceous/Paleogene boundary of ODP Hole 117-1049C at Blake Nose, Northwest Atlantic (Appendix A). 361 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 90-590B in the southwestern Pacific. 2381 records from Hawaiian Algal Database. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 6278 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 587 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 239 records from Planktic foraminifera counts at CTD station M39/4_352CTD-11. 215 records from Total foraminifera counts from multinet M31/3_MSN921. 87 records from Artenvielfalt des "Grünen Klassenzimmers". 76 records from Faunal assemblage of sediment core TR149-37. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 359 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 124 records from Stable isotope data and sedimentology of core SO42-74KL. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 149 records from Total foraminifera counts from multinet M31/2_MSN888. 147 records from Total foraminifera counts from multinet M31/2_MSN889. 96 records from Total foraminifera counts from multinet M31/2_MSN894. 91 records from Total foraminifera counts from multinet M31/2_MSN897. 202 records from Total foraminifera counts from multinet M31/3_MSN900. 206 records from Total foraminifera counts from multinet M31/3_MSN907. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 113 records from Total foraminifera counts from multinet M31/2_MSN890. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 119 records from Total foraminifera counts from multinet M31/2_MSN892. 128 records from Total foraminifera counts from multinet M31/
Keywords: GBIF; biodiversity; species occurrences